Effect of growing temperature on root carbohydrate content and postharvest asparagus tip breakdown - Collings, Emma R.; Alamar, M. Carmen; Terry, Leon A. (Wiley, 2025)
BACKGROUND Tip breakdown has been identified as the main issue causing deterioration in asparagus quality during storage; however, the underlying mechanisms responsible for its development are unknown. Previous work showed higher incidence of tip breakdown occurring later in the season, when growing temperature was higher. Spears from two growing conditions (cooler vs warmer) were harvested throughout the season to assess tip breakdown incidence and quality attributes (asparagine and non‐structural carbohydrates) during storage, with the aim of enhancing understanding and identifying potential biomarkers of this physiological disorder. Root samples were also collected just after harvest to determine if storage root carbohydrate content was associated with a predisposition to tip breakdown. RESULTS Rapid growth due to warmer temperatures (up to 45 °C) resulted in spears with lower sugar content and higher incidence of tip breakdown in comparison with cooler conditions. Asparagine slowly increased through the season (7 to 11 mg g−1 DW) with no differences between growing conditions, suggesting that it is not a biomarker for tip breakdown. Pre‐season spears (warm temperature only) had double the amount of sugar in comparison with early season spears, with no incidence of tip breakdown despite an extended storage period (up to 18 days at 7 °C). Sugar concentration in roots was similar between growing conditions and between pre‐ and early season despite clear differences in spear sugar content. CONCLUSION These results showed a strong positive link between cooler growing conditions, high spear sugar content, and low susceptibility to tip breakdown, which was not reflected in root sugar concentrations. However, further research is needed to understand the molecular mechanisms responsible for tip breakdown.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Asparagus officinalis; asparagine; storage; sugars; Food Science; 40 Engineering